The Ukrainian Public Administration of Territorial Seas: A European Example - Кормич, Борис Анатолійович; Кормич, Б. А.; Кормич, Борис Анатольевич; Kormych, Borys A.; Аверочкіна, Тетяна Володимирівна; Аверочкіна, Т. В.; Аверочкина, Татьяна Владимировна; Averochkina, Tetiana V.; Гаверський, Віталій Валерійович; Гаверський, В. В.; Гаверский, Виталий Валерьевич; Gaverskyi, Vitaliy V. (Wolters Kluwer, 2020)
The article evaluates the modern doctrine of territorial sea administration. The article views the administration of coastal state as an application and enforcement of UNCLOS based regimes of maritime zones. The article examines the legal regulation of the territorial sea. It also studies the process of overlapping and interaction between different administrative and legal regulations applicable to a given maritime zone. The features of such regulation are pointed out based upon the combination and mutual influence of international, EU and national law. Ukraine’s experience in administering the territorial sea after the illegal annexation of Crimea is studied. The pros and cons of EU concept of Maritime spatial planning with respect to the demands of protection and security are revealed in the context of hybrid conflicts.

У статті дається оцінка сучасної доктрини управління територіальним морем. У статті розглядається як застосування, так і виконання в управлінні прибережною державою режимів морських зон, заснованих на UNCLOS. У статті розглядається правове регулювання територіального моря. Також вивчається процес дублювання та взаємодії різних адміністративно-правових норм, що застосовуються до даної морської зони. Особливості такого регулювання відмічаються на основі поєднання та взаємовпливу міжнародного права, законодавства ЄС та національного законодавства. Вивчається досвід України в управлінні територіальним морем після незаконної анексії Криму. Плюси та мінуси концепції ЄС морського просторового планування з урахуванням вимог захисту та безпеки розкриваються в контексті гібридних конфліктів.

В статье дается оценка современной доктрине управления территориальным морем. В статье рассматривается как применение, так и выполнение в управлении прибрежным государством режимов морских зон, основанных на UNCLOS. В статье рассматривается правовое регулирование территориального моря. Также изучается процесс дублирования и взаимодействия различных административно-правовых норм, применяемых к данной морской зоне. Особенности такого регулирования отмечаются на основе сочетания и взаимовлияния международного права, законодательства ЕС и национального законодательства. Изучается опыт Украины в управлении территориальным морем после незаконной аннексии Крыма. Плюсы и минусы концепции ЕС морского пространственного планирования с учетом требований защиты и безопасности раскрываются в контексте гибридных конфликтов.
Kormych B. The Ukrainian Public Administration of Territorial Seas: A European Example / В. Kormych, Т. Averochkina, V. Gaverskyi // European Energy and Environmental Law Review. – V. 29 (2). – Wolters Kluwer, 2020. – Р. 26 – 38.
Keywords: public administration; territorial sea; maritime zone; coastal state jurisdiction; marine environment; Ukraine; державне управління; територіальне море; морська зона; юрисдикція прибережної держави; морське середовище; Україна; государственное управление; территориальное море; морская зона; юрисдикция прибрежного государства; морская среда; Украина; Research Subject Categories::LAW/JURISPRUDENCE